Analisis Keterlambatan Proyek Renovasi Pura di Kabupaten Jembrana (Studi Kasus: Keterlambatan Proyek Renovasi Pura Dalem Desa Adat Kaliakah Kangin dan Kaliakah Kauh) - I Gusti Kade Supartha; Komang Agus Ariana; Putu Ariawan; I Gusti Ngurah Putu Dharmayasa; Ketut Nuraga (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
If planning and control are not carried out properly, temple renovation projects often experience delays. This paper examines the dangers associated with delays in temple renovation projects in Jembrana Regency. With a sample of 30 respondents, this study uses a quantitative descriptive methodology. Statistical product and service solution software, or SPSS, was used to process the data. Data analysis techniques include factor analysis, validity testing, and reliability testing. The results of the analysis of the causes of delays are: factors: Frequent work delays, Renegotiating the Implementation Time by Submitting an Addendum to the Contract Extension of the Implementation Time, Submitting Additional Contract Value Funds based on MC.0% Calculations, Inaccurate Labor Planning, (Ineffective Communication and Coordination within the Contractor Organization, Changes in the Scope of Work/Construction Details, Material Damage During Delivery, Delays in Approval of Designs/Working Drawings